2009
DOI: 10.4161/oxim.2.2.8160
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Antioxidant Status in Head and Neck Squamous Cell Carcinoma Patients

Abstract: Oxidative stress, a consequence of an imbalance between the formation and inactivation of reactive oxygen species, may be involved in the pathogenesis of many diseases including cancer. To evaluate the magnitude of oxidative stress, a study on the plasma levels of superoxide dismutase, total thiols, ascorbic acid and malondialdehyde (MDA) has been done in head and neck squamous cell carcinoma patients before the start of any oncological treatment and compared with healthy controls. The specific activity of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…These findings show that oxidative stress is elevated in cancer patients as evidenced by elevated levels of lipid peroxidation products -malondialdehyde (MDA). 10 In the study conducted by Subramanyam et al, the decreased levels of glutathione peroxidase activity and total antioxidant capacity, and increased malondialdehyde, glutathion reductase, were observed in cervical cancer patients when compared to healthy controls. 11 Decreased levels of TAC in patients with lung cancer, correlating with oxidative damages of proteins, were acknowledged by Erhola et al 12 Similar observations were made by Hietanen et al with regard to patients suffering from breast or prostate cancer, as well as colorectal carcinoma (CC), which was especially significant compared to the results of the research described herein.…”
Section: Discussionmentioning
confidence: 99%
“…These findings show that oxidative stress is elevated in cancer patients as evidenced by elevated levels of lipid peroxidation products -malondialdehyde (MDA). 10 In the study conducted by Subramanyam et al, the decreased levels of glutathione peroxidase activity and total antioxidant capacity, and increased malondialdehyde, glutathion reductase, were observed in cervical cancer patients when compared to healthy controls. 11 Decreased levels of TAC in patients with lung cancer, correlating with oxidative damages of proteins, were acknowledged by Erhola et al 12 Similar observations were made by Hietanen et al with regard to patients suffering from breast or prostate cancer, as well as colorectal carcinoma (CC), which was especially significant compared to the results of the research described herein.…”
Section: Discussionmentioning
confidence: 99%
“…However other reports have demonstrated the opposite: a low or undetectable lipid peroxidation, as well as HNE content, such as in hepatomas (Dianzani, 1993). Several studies have shown elevated lipid peroxidation markers in the sera, plasma or urine of breast carcinoma (Hung et al, 1999;Chandramathi et al, 2009), cervical intraepithelial neoplasia and carcinoma of the cervix (Looi et al, 2008), head and neck squamous cell carcinoma (Gupta et al, 2009) and prostate tumor (Kotrikadze et al, 2008), compared to healthy controls. However, these extratumoral measurement are likely, at least partly, to reflect generalized oxidative stress and /or inflammation in the whole body.…”
Section: Hne Content In Human Cancersmentioning
confidence: 99%
“…For example, the causative link between peroxidation of lipids and lipoproteins, and several multifactorial diseases including CVD and cancer has been stressed in several reports (Halliwell, 2000;Atmani et al, 2009;Gupta et al, 2009;Rice-Evans, 2001). Lipid peroxidation and protein oxidation play also a role in the progression of Alzheimer's disease (Sultana et al, 2006).…”
Section: Rons and Chronic Diseasesmentioning
confidence: 99%
“…Peroxides formed during lipid peroxidation processes can decompose into a vast array of toxic carbonyl products such as malondialdehyde (MDA), playing among others a role in the carcinogenesis process by interacting with cellular DNA, yielding e.g. DNA-MDA adducts that appear to be promutagenic (Gupta et al, 2009). The adverse effects of RONS are also involved in different stages of carcinogenesis by causing structural DNA damage, interacting with oncogenes, tumor suppressor genes or immunological mechanisms (Gupta et al, 2009).…”
Section: Rons and Chronic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation